Fog collection on a superhydrophobic/hydrophilic composite spine surface. Issue 16 (4th March 2020) - An, Qier; Wang, Jinshu; Zhao, Feng; Wang, Lei
Abstract : The fog collection phenomenon on the superhydrophobic/hydrophilic composite spine structure. Abstract : Inspired by numerous plants and animals living in arid conditions, a composite surface with the fog collection capacity has been fabricated in this study. The surface is composed of polydimethylsiloxane-based spine-arrays and a ZnO micron structure. Two wetting properties are integrated on the surface of the spine structure; the tip of spine is processed as hydrophilic and other parts such as the root region of spine and the base are processed as superhydrophobic. When the surface is in the saturated fog flow with a specific tilt angle, the fog deposits on spines and forms condensed droplets; then, the droplets fall off the surface due to gravity. Further, a new cycle of fog collection begins. In this study, we find that the percentage of the hydrophilic tip in the overall spine structure length, the distance between two spines and the tilt angle of surface are the key factors for improving the efficiency of fog collection. Such a composite surface might be an ideal platform for fog collection from air.